SOCAL CONDITIONALITY OF ESTABLISHING CRIMINAL LIABILITY FOR ADVERTISING OF NARCOTİC DRUGS, THEIR ANALOGUES OR PSYCHOTROPIC SUBSTANCES, AS WELL AS PREPARATİONS CONTAINING POTENT SUBSTANCES - Captain Erlan Daniyarovich Baratov (American Journals Publishing, 2023)
Today, in our society, the Republic of Uzbekistan is addicted to drugs international community to combat illicit trafficking of substances special attention is being paid to the full fulfillment of its obligations. This article is about drug addiction, its negative consequences, and against the scourge of addiction strong legal frameworks developed in our country to fight illuminated.
Keywords: narcotic drugs, psychotropic substances, international community, illegal circulation, negative consequences.